Circulatory Arrest due to Retrograde Embolization of a Transapically Implanted Aortic Valve Prosthesis with Subsequent Inversion and Left Ventricular Outflow Occlusion. Issue 7 (1st April 2016) - Reske, Alexander; Ibrahim, Karim; Reske, Andreas W.; Kappert, Utz
Abstract : An 82-year-old man required aortic valve replacement because of aortic stenosis. A transapical approach was chosen to reduce surgical mortality. Initially, echocardiography and fluoroscopy confirmed correct valve positioning. Shortly thereafter, progressive paravalvular leakage, embolization of the valve prosthesis into the ventricle, and subsequent inversion of the prosthesis with complete left ventricular outflow occlusion were observed by echocardiography. Left ventricular outflow occlusion resulted in immediate circulatory arrest. We immediately converted to on-pump surgical aortic valve replacement. Cardiac output was restored once the valve was replaced. The patient fully recovered. This case report highlights the importance of periprocedural transesophageal echocardiography, which instantly detected the malpositioned valve and guided emergency management of this severe complication.